Clinical and molecular predictors of fibrotic progression in essential thrombocythemia: A multicenter study involving 1607 patients. Issue 11 (6th September 2021) - Loscocco, Giuseppe G.; Guglielmelli, Paola; Gangat, Naseema; Rossi, Elena; Mannarelli, Carmela; Betti, Silvia; Maccari, Chiara; Ramundo, Francesco; Jadoon, Yamna; Gesullo, Francesca; Ceglie, Sara; Paoli, Chiara; et al.
Abstract: The current retrospective study involving a total of 1607 patients was designed to identify clinical and molecular variables that were predictive of inferior myelofibrosis‐free survival (MFS) in WHO‐defined essential thrombocythemia (ET), utilizing three independent patient cohorts: University of Florence, Italy ( n = 718); Mayo Clinic, USA ( n = 479) and Policlinico Gemelli, Catholic University, Rome, Italy ( n = 410). The Florence patient cohort was first examined to identify independent risk factors for MFS, which included age > 60 years (HR 2.5, 95% CI 1.3–4.9), male sex (2.1, 1.2–3.9), palpable splenomegaly (2.1, 1.2–3.9), CALR 1/1‐like or MPL mutation (3.4, 1.9–6.1) and JAK2 V617F variant allele frequency > 35% (4.2, 1.6–10.8). Subsequently, an operational molecular risk category was developed and validated in the other two cohorts from Mayo Clinic and Rome: "high molecular risk" category included patients with JAK2 V617F VAF >35%, CALR type 1/1‐like or MPL mutations; all other driver mutation profiles were assigned to "low molecular risk" category. The former, compared to the latter molecular risk category, displayed significantly higher risk of fibrotic transformation: Florence cohort with respective fibrotic transformation risk rates of 8% vs. 1.2% at 10 years and 33% vs. 8% at 20 years ( p < 0.001; HR 6.1; 95% CI 3.2–11.7); Mayo Cohort, 16% vs. 7% at 10 years and 44% vs. 25% at 20 years ( p < 0.001; HR 2.5; 95% CI 1.6–4.1); and Rome cohort 7.8% vs. 4.6% at 10 years and 31.2% vs. 7.1% at 20 years ( p = 0.007, HR 2.7; 95% CI 1.3–5.8). The present study provides practically useful risk signals for fibrotic transformation in ET and facilitates identification of patients who require close monitoring and appropriate counseling.